Interplay between structural parameters and reactivity of Zr 6 -based MOFs as artificial proteases - Loosen, Alexandra; de Azambuja, Francisco; Smolders, Simon; Moons, Jens; Simms, Charlotte; De Vos, Dirk; Parac-Vogt, Tatjana N. (Chemical science (Cambridge), 2020)
Structural parameters influencing the reactivity of metal–organic frameworks (MOF) are challenging to establish. However, understanding their effect is crucial to further develop their catalytic potential. Here, we uncovered a correlation between reaction kinetics and the morphological structure of MOF-nanozymes using the hydrolysis of a dipeptide under physiological pH as model reaction. Comparison of the activation parameters in the presence of NU-1000 with those observed with MOF-808 revealed the reaction outcome is largely governed by the Zr 6 cluster. Additionally, its structural environment completely changes the energy profile of the hydrolysis step, resulting in a higher energy barrier Δ G ‡ for NU-1000 due to a much larger Δ S ‡ term. The reactivity of NU-1000 towards a hen egg white lysozyme protein under physiological pH was also evaluated, and the results pointed to a selective cleavage at only 3 peptide bonds. This showcases the potential of Zr-MOFs to be developed into heterogeneous catalysts for non-enzymatic but selective transformation of biomolecules, which are crucial for many modern applications in biotechnology and proteomics.